Bankruptcy Rates among NFL Players with Short-Lived Income Spikes - Carlson, Kyle; Kim, Joshua; Lusardi, Annamaria; Camerer, Colin F. (American Economic Review, 2015)
We test for consumption smoothing using bankruptcy data on players in the National Football League (NFL), who typically earn several million dollars during an income spike that lasts a few years. The life-cycle hypothesis predicts that players should save substantially while playing and then have little risk of bankruptcy post-NFL. However, players in our sample begin to file for bankruptcy soon after they stop playing and continue filing at a high rate through at least the first 12 years of retirement. Players' total earnings and career lengths have surprisingly little effect on the risk of bankruptcy.